Development of an efficient immersed-boundary method with subgrid-scale models for conjugate heat transfer analysis using large eddy simulation. (May 2019) - Lee, Sangjoon; Hwang, Wontae
Highlights: Immersed-boundary based LES method developed for conjugate heat transfer problems. An optimized flood-fill algorithm enhances thermal interpolation performance. LES successfully predicted the turbulent flow and thermal characteristics. Fluid-solid interaction significantly affects thermal characteristics of the flow. Abstract: A numerical procedure for conjugate heat transfer (CHT) analysis based on an immersed boundary (IB) method for large eddy simulation (LES) has been developed. The dynamic subgrid-scale (SGS) stress and heat flux models are implemented in the solver. Since discrepancy between the computational grid and solid-fluid interface generally exists, interpolation of thermal properties at the interface is necessary for the current method. Accordingly, an efficient interpolation scheme using the modified flood-fill algorithm is applied. In order to validate the capability of the developed method, three different CHT cases with turbulent flow were examined: channel flow between heated slabs, thermally-driven flow in a closed cavity, and crossflow around a heated circular cylinder. Compared to cases that just utilized an isothermal or constant-heat-flux boundary condition, when the CHT method was properly implemented, results more closely matched experimental data and existing correlations.